(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Epilepsy is a neuronal disorder that is observed globally but still it is not explored very well in most parts of the world. Objective: The aim of our study was to determine the types of epilepsies along with their treatment strategies among patients attending the outdoor epilepsy clinic in a referral tertiary care hospital. Methodology: This cross sectional study was carried out from the records of weekly epilepsy clinic of Department of Neurology at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from January 2018 to August 2019. Data were collected through a predesigned questionnaire containing information about demography, clinical features, EEG and imaging findings and treatment of patients. Results: A total number of 1832 patients were recruited. There was a male (55.3%) and urban (61.1%) predominance. Most (75.1%) of the patients were young (age range from 10 to 29 years). A large number of patients were student (44.4%) and 24.2% were unemployed. The duration of epilepsy in most patients were less than 5 years (40.7%). 58.3% patients took various forms of indigenous treatment prior to attending this clinic. 54.7% patients had no comorbid illness. EEG was abnormal in 34.5% patients of which 24.4% had focal abnormality and 10.1% had generalized epileptic discharge. In brain imaging (CT/MRI) only 16.4% showed abnormal findings. 49.5% patients were suffering from generalized epilepsy whereas 44.6% had partial epilepsy. Among the generalized epilepsy group, most of them had generalized tonic clonic seizure (GTCS) (75.4%), while 8.9% had absence seizure and 7.9% had tonic seizure. In partial epilepsy group, the majority were secondary generalized seizure (74.7%), followed by complex partial seizure (CPS) (18.7%) and simple partial seizure (6.6%).42.7% patients got single antiepileptic drug whereas 37.4% patients received dual drug. Polytherapy (three or more drugs) were prescribed in 14% patients. Valproic acid was the highest prescribed drug (29.3%) either as monotherapy or in combination. Carbamazepine (27.4%) was the second common drug followed by Levetiracetam (15.1%). Conclusion: Epilepsy affects almost all groups of the society. Most of the patients remain seizure-free with judicious anti-epileptic drugs. Therefore, more effort is needed for early accurate diagnosis and appropriate treatment of epilepsy Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 3-8